The Significance of the Relationship between Main Effects and Side Effects for Understanding the Knobe Effect - Andrzej Waleszczyński; Michał Obidziński; Julia Rejewska (Organon F, 2019)
The characteristic asymmetry in ascribing intentionality, known as the Knobe effect, is widely thought to result from the moral evaluation of the side effect. Existing research has focused mostly on elucidating the ordinary meaning of the notion of intentionality, while less effort has been devoted to the moral conditions associated with the analyzed scenarios. The current analysis of the moral properties of the main and side effects, as well as of the moral evaluations of the relationship between them, sheds new light on the influence of moral considerations on the attribution of intentionality in the Knobe effect. The moral evaluation of the relationship between the main and side effects is significant in that under certain circum-stances it cancels asymmetry in intentionality ascription.